Cross-ecosystem utilizing primed seeds of upland rice varieties for enriching crop diversity at riparian wetland during dry season - ROFIQOH PURNAMA RIA; BENYAMIN LAKITAN; FIRDAUS SULAIMAN; KARTIKA KARTIKA; RUJITO AGUS SUWIGNYO (Society for Indonesian Biodiversity, 2020)
Abstract. Ria RP, Lakitan B, Sulaiman F, Kartika K, Suwignyo RA. 2020. Cross-ecosystem utilizing primed seeds of upland rice varieties for enriching crop diversity at riparian wetland during dry season. Biodiversitas 21: 3008-3017. Cultivation of rice during second growing season at riparian wetlands in Indonesia must deal with drought conditions at reproductive stage. Seed priming can speed up seed emergence and produces vigorous seedlings. Objective of this study was to screen upland rice varieties which were positively responded to seed priming and tolerant to drought during late vegetative and/or reproductive stage. Results of this study indicated that osmo-priming showed positive effects on seed emergence, percentage of germinated seed, and time to reach 50% germination. Effects of osmo-priming on seedling growth did not go beyond four weeks after seedlings had been transplanted. Among nine varieties screened, Inpago 10 exhibited better response to seed priming during late vegetative stage as it produced the highest number of tillers and total leaf area. However, at harvest, osmo-priming with 20% PEG lowered filled spikelet and weight of 100 grains but did not affect yield. Drought during late vegetative stage lessened number of tillers but after drought-treated plants recovered during reproductive stage, percentage of filled spikelet and grain size were comparable to those of control plants. Meanwhile, drought imposed during reproductive stage decreased percentage of filled spikelet and grain yield. Despite its better performance under drought conditions, leaf rolling score was higher during heading stage in Inpago 10. This phenomenon indicated that leaf rolling was not forced by drought, rather it was a quick response of Inpago 10 variety to limit water loss due to transpiration.